Social and cultural impact of grand mosque Durres on the development of Muslim community, Albania - Soomro , Ali Raza; Basha, Brunilda; Aripin, Srazali (2013)

(untitled)
The first contacts of Albanians to Islam are proven to be relatively early in the medieval centuries. Due to geographical situation, Albania was densely frequented by Turkish and Arab missionaries; no matter it was a commercial, religious or military purpose. The Islamization of Albanian Community went all the way through progressive growth as it is reflected from the customs of the community as well as from their architecture. The mosques remained the focal points for teachings of Islam and were considered as the core of the Muslim society as the mosques played the role not only for growing peoples religious needs but also had significant impact on the overall development of the community. From the beginning, the mosques were the places for prayer, meditation, religious instructions, political discussions, and learning places. Unfortunately the role of the mosques at the present time has been minimized only in performing daily prayers and few other religious activities. Hence today the mosques do not play sufficient role in social and cultural developments of the Albanian Muslim community especially the Muslims living in Durres city of Albania. This paper attempts to analyse the social and cultural role of the Great Mosque Duress, Albania and how far it has the impact on the development of the Muslim Community living in Durres. In this regard the case study of Great Mosque of Durres has been conducted to unfold the facts of deterioration of Muslim life style in Durres. Eventually this study will reach to a model design with some necessary added functions so that the new model design of Mosque should play the vital role in revitalizing the Islamic practices as it was observed in the past to develop the Muslim community in Durres, Albania